Denmark : Financial Sector Assessment Program; Technical Note; Pensions with Profit Contracts. (IMF Staff Country Reports; Country Report ;, 2007)
This technical note examines pensions with profit contracts in Denmark. The Danish life insurance and pension sector is sensitive to a range of risks on both the asset and liability side of the balance sheet. One of the principal vulnerabilities for the sector arises out of the requirement to achieve a high guaranteed return for the duration of 'in-force' policies. Although several measures have been implemented to increase provisions and capital, and for hedging interest rate risk through derivatives, the overall risk in the pension sector still needs to be closely monitored.